2
$\begingroup$

Say we have an expression like

$$\frac{\sqrt{\frac{k}{g}}}{k}=\frac{1}{\sqrt{gk}}$$

How do we get from the left hand side, to the right hand side? If we simplify the square root

$$\sqrt{\frac{k}{g}}=\frac{\sqrt{k}}{\sqrt{g}}$$

Then

$$\frac{\sqrt{k}}{\sqrt{g}}\times \frac{1}{k}=\frac{\sqrt{k}}{k\sqrt{g}}$$

Then multiply through by $\sqrt{k}$ and cancel out $k$?

$$\frac{\sqrt{k}}{k\sqrt{g}}=\frac{k}{k\sqrt{g}\sqrt{k}}=\frac{1}{\sqrt{gk}}$$

Is that correct?

$\endgroup$
  • 4
    $\begingroup$ Yes, that’s right. $\endgroup$ – KM101 Nov 5 '18 at 15:29
0
$\begingroup$

$$\frac{\sqrt{\frac{k}{g}}}{k}=\frac{\sqrt \frac kg}{\sqrt\frac{k^2}{1}}=\sqrt\frac{k \over g}{k^2 \over 1}=\sqrt\frac{k}{gk^2}=\sqrt\frac{1}{gk}={\sqrt{1} \over \sqrt{gk}}={1 \over \sqrt{gk}}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.